THE EFFECT OF COMPETENCE, WORK EXPERIENCE, AND INFORMATION TECHNOLOGY MASTERY ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE IN THE REGIONAL SECRETARIAT OF THE CITY OF BATAM - Daffin Mandala Putra; Chablullah Wibisono; Sriyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to determine the direct and indirect relationships between competency, work experience, and information technology mastery on employee performance through work motivation as an intervening variable at the Regional Secretariat of Batam City. The population can provide useful information or data for a study. The population in this study consisted of 144 civil servants working at the Regional Secretariat of the Batam City Government. In this study, the sampling technique used is nonprobability sampling, specifically saturated sampling (census). The sample used in this study is the entire population of 144 civil servants at the Regional Secretariat of the Batam City Government. Data were collected via questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple regression analysis, and path analysis.The results of the study indicate that there is a direct and indirect influence between the variables of competence, work experience, and information technology mastery on employee performance through work motivation as an intervening variable at the Regional Secretariat of the Batam City Government.